Personal Growth Initiative of Millenials Woman Leader in Indonesia: a Qualitative Study - Dhini Rama Dhania; Suryanto Suryanto; Fendy Suhariadi Fendy Suhariadi; Fajrianthi Fajrianthi (Universitas Ahmad Dahlan, 2021)
Today organizations around the world are dominated by millennial employees and are in the career development stage as leaders. Personal growth is an essential aspect of leadership, especially for female leaders who have different experiences from male leaders. When someone is consciously, intensely, and engaged in the process of personal growth, this is called a personal growth initiative that has a positive function on life and the organization. For this reason, this study aims to understand how personal growth initiatives are on millennial women leaders. This research uses a phenomenological qualitative approach. Data were collected using semi-structured interviews with 5 millennial women leaders. The results show three main themes: (1) There are different meanings related to personal growth initiatives in female leaders, (2) There are several obstacles that originate from outside and within millennial women leaders in the process of personal growth initiatives, (3) factors which drive the personal growth initiative of millennial women leaders comes from internal and external factors. The findings in this study are expected to be a meaningful contribution to understanding the personal growth initiative of millennial women leaders.Â